Assessment of the profile of victims of femur fractures treated at an urgent and emergency hospital in the Brazilian western Amazon (Research, Society and Development, 2022)
Femur fractures have higher morbidity and mortality at all levels of health care. Thus, falls in the elderly are quite frequent as they lead to a decrease in functional capacity and serious consequences for these patients. Traffic accidents are relevant, affecting more young male adults, with recklessness being the main cause of these accidents. The profile of victims of femur fractures treated at an urgent and emergency hospital in Porto Velho/RO was evaluated, through the stratification of the data presented by sex, age group, affected side and trauma mechanism. The methodology of this study was carried out through data collected from medical records, deliberated by the HOSPUB system. The results were evaluated the number of traumatic admissions by orthopedics in the period from January to April of the year 2021, totaling 2,043 patients treated in the red room and outpatient clinic, of this total 63 are femur fracture 3.08% (63/2,043), being the distribution of these in the months; January 41.2% (26/63), February 17.4% (11/63), March 25.3% (16/63) and April 15.8% (10/63). The gender variable was evaluated, among the patients seen, there was a predominance of males in the age group of 21-49 years 30.5% (19/63) being equivalent when compared to other results, this being the most affected by accidents and violence. It is concluded that the profile of victims with femur fractures is predominant in females when treating the elderly, where the main cause is falls. The highest prevalence among young adults is male, with motorcycle accidents as the main trauma mechanism.